Video-guided calibration of an augmented reality mobile C-arm - Chen, Xin; Naik, Hemal; Wang, Lejing; Navab, Nassir; Fallavollita, Pascal (International Journal of Computer Assisted Radiology and Surgery, 2014)
Purpose: The augmented reality (AR) fluoroscope augments an X-ray image by video and provides the surgeon with a real-time in situ overlay of the anatomy. The overlay alignment is crucial for diagnostic and intra-operative guidance, so precise calibration of the AR fluoroscope is required. The first and most complex step of the calibration procedure is the determination of the X-ray source position. Currently, this is achieved using a biplane phantom with movable metallic rings on its top layer and fixed X-ray opaque markers on its bottom layer. The metallic rings must be moved to positions where at least two pairs of rings and markers are isocentric in the X-ray image. The current “trial and error” calibration process currently requires acquisition of many X-ray images, a task that is both time consuming and radiation intensive. An improved process was developed and tested for C-arm calibration.
CRIS-Team Scopus Importer:2023-03-08
Keywords: C-arm fluoroscopy; Calibration; Medical augmented reality; Multi modalities; Orthopedic and trauma surgery; Video guidance; Visualization